Development of Ethnomathematics-Based Teaching Materials with Problem Based Learning Model to Improve Critical Thinking Skills - Maysun Salwaa, Nadiya; Mulyono (EduGrows: Education and Learning Review, 2025)
Students' critical thinking skills in mathematics learning are still relatively low, mainly because the learning process is not contextual and student-centered. This study aims to develop mathematics teaching materials with an ethnomathematics nuance using the Problem Based Learning (PBL) model to improve students’ critical thinking skills on the topic of angle relationships for seventh-grade junior high school students. The research employed a Research and Development (R&D) approach with the ADDIE stages (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were students of class VII C. The research instruments consisted of expert validation sheets, student response questionnaires, and a critical thinking skills test. The results of expert validation indicated that the teaching materials fell into the “very valid” category with an average score of 3.54. Student responses showed the teaching materials to be “very practical” with an average score of 3.58, while teacher responses also indicated “very practical” with an average score of 3.7. The effectiveness test showed an increase in students’ pretest and posttest scores, as evidenced by the N-gain results, although only within the medium category. In addition, 50% of students achieved learning mastery above the Minimum Mastery Criteria (KKM).